Examining Classroom Contexts in Support of Culturally Diverse Learners' Engagement: An Integration of Self-Regulated Learning and Culturally Responsive Pedagogical Practices. - Aloysius C. Anyichie; Deborah L. Butler; Nancy E. Perry; Samson M. Nashon (EARLI, 2023)
Research shows that culturally diverse students are often disengaged in multicultural classrooms. To address this challenge, literatures on self-regulated learning (SRL) and culturally responsive teaching (CRT) both document practices that foster engagement, although from different perspectives. This study examined how classroom teachers at schools that enrol students from diverse cultural communities on the West Coast of Canada built on a Culturally Responsive Self-Regulated Learning Framework to design complex tasks that integrated SRL pedagogical practices (SLPPs) and culturally-responsive pedagogical practices (CRPPs) to support student engagement. Two elementary school teachers and their 43 students (i.e., grades 4 and 5) participated in this study. We used a multiple, parallel case study design that embedded mixed methods approaches to examine how the teachers integrated SRLPPs and CRPPs into complex tasks; how culturally diverse students engaged in each teacher's task; and how students' experiences of engagement were related to their teachers' practices. We generated evidence through video-taped classroom observations, records of classroom practices, students' work samples, a student self-report, and teacher interviews. Overall findings showed: (1) that teachers were able to build on the CR-SRL framework to guide their design of an CR-SRL complex task; (2) benefits to students' engagement when those practices were present; and (3) dynamic learner-context interactions in that student engagement was situated in features of the complex task that were present on a given day. We close by highlighting implications of these findings, limitations, and future directions.